Impact of management of poorly functional natural drains on water table, field workability and crop yield - SHARMA, R K; KHUSHWAH, S S (The Indian Journal of Agricultural Sciences, 2013)
An investigation was conducted to assess the impact of cleaning of natural drains from heavy infestation of predominant aquatic weed lpomoea carnea at Baikhedi village of Tawa Command. Among various control measures, 1 spray of 2,4-D EE@ 22 kg ai/ha in March/April followed by manual cleaning and burning of dried stubble was found suitable with weed control efficiency as 82.5%. This measure has benefitted the drainage area in various ways. It controlled the water table by 24 cm. The number of occurrence of shallow water table conditions reduced by 20%. The time (in days) required for the field to become workable after pre-sowing irrigatiOn reduced by 3,3,6 and 10 days under excellent, good, fair and poor drainage condition respectively. The average increase in yield of’Lok I’ wheat was observed around 16 to 20% compared to yield levels obtained prior to cleaning operation. fhe initial cost of cleaning waS around Rs 2 716/km for 10m wide section of the drain. The cost of cleaning of resprouted weed in the subsequent 2 years came around 11% ano 9% of the initial cost respectively. Adoption of this measure generated 778-man-days employment to villagers. Cleaning of poorly funtional natural drains from infestation of Ipomoed carnea weed maintains good flow of excess water which in turn reduces waterlogging hazards and improves the productivity as well as workability of the area.